PEMBERDAYAAN MASYARAKAT DI DESA WISATA CIKAKAK KECAMATAN WANGON KABUPATEN BANYUMAS - Ayu Vela Handayani; Maesaroh Maesaroh; Nina Widowati (Journal of Public Policy and Management Review, 2023)
Banyumas Regency is one of the active districts in accelerating the tourism industry. Cikakak Tourism Village is the only tourism village with an advanced category in Banyumas Regency. This is proven through the Decree of the Banyumas Regent Number /556/166/Year 2020. Management in the development of the Cikakak Tourism Village involves direct community participation to empower the community which aims to realize community independence. The purpose of this research is to find out the stages of community empowerment in the management of Cikakak Tourism Village and the inhibiting factors for the implementation of community empowerment in the management of Cikakak Tourism Village. This research uses a descriptive method with a qualitative approach. The research site is Cikakak Tourism Village. Data collection techniques in this study through in-depth interviews, observation, and documentation. After the data is collected, the writer will then carry out an analysis using Miles Huberman's analysis technique which includes three stages, namely data reduction, data presentation, and drawing conclusions. The validity of the research data was carried out by source triangulation. The results of the study were seen from the three stages in community empowerment, namely the stages of awareness, capacity building, and empowering in the Cikakak Tourism Village that had not gone as expected, as evidenced by the obstacles encountered at each stage of community empowerment. The inhibiting factors for community empowerment in the Cikakak Tourism Village are organization, human resources, and business capital.